Analisis Perencanaan Audit dan Kompetensi Auditor pada Kualitas Audit di Perwakilan BPKP Provinsi Bali - Azizi, Ahmad Fajrin; Muliartha, I Ketut (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p02, 2018)
Audit planning and auditor competence are determinants of audit quality carried out by auditors. Audit planning and auditor competence are needed to conduct audit judgments where the accuracy of judgment produced by the auditor in completing the audit work has an influence on the final conclusion. Auditors in conducting judgments must be carried out with audit planning and adequate auditor competence. The purpose of this study was to analyze the influence of audit planning and auditor competency on audit quality at the Representative of the Bali Provincial Finance and Development Supervisory Agency (BPKP). This research was conducted at the Bali Provincial BPKP Representative Office. The number of samples taken were 77 Auditor Functional Officers (PFA), with purposive sampling method with PFA requirements that had auditor certification and were not carrying out education outside Bali during sampling. Data collection is done through questionnaire techniques. The analysis technique used is multiple linear regression using SPSS. The results of the analysis show that there is a positive and significant influence between audit planning and auditor competence on audit quality. This means that audit planning and adequate auditor competence can maintain audit quality produced by the Auditor's Functional Officer. Keywords: audit planning, auditor competence, audit quality